Ubiquitin-proteasome system: a potential participant and therapeutic target in antiphospholipid syndrome - Wang, He; Tan, Yuan; Liu, Qi; Yang, Shuo; Cui, Liyan (Frontiers in Immunology, 2025)
APS (antiphospholipid syndrome) is an autoimmune disease characterized by thrombosis, pregnancy complications and persistent elevation of aPLs (antiphospholipid antibodies). Dysfunction of innate immune cells, ECs (endothelial cells), platelets and trophoblast cells are central to the development of APS. The UPS (ubiquitin-proteasome system) is a highly conserved post-translational modification in eukaryotes. Imbalance of the UPS potentially disrupts the protein homeostasis network and provokes prothrombotic and proinflammatory signaling during APS progression. In vivo, low-dose proteasome inhibitors are believed to effectively inhibit the production of proinflammatory factors and the clinical manifestations of APS. In this review, we would like to summarize the likely contribution of dysregulated UPS to the pathogenesis of APS. Given the significant progress made in understanding the molecular mechanisms of the UPS and how alterations in the UPS lead to the development of autoimmune diseases, targeting the UPS may represent a novel therapeutic strategy.